Metaverses and Business Transformation - Polyviou, Ariana; Pappas, Ilias O. (My University, 2022)
Metaverses refer to virtual worlds which enable the interaction between users and simulate people, places and things of the physical world. The wider use of metaverses can disrupt how we interact and bring a plethora of implications for businesses and society. While the term metaverse received increased attention recently due to the interest of tech giants, researchers have been exploring virtual world interactions for over a decade. In light of new exciting metaverse implementations, it is necessary to consolidate information via existing research on how the use of metaverses can transform businesses. As a first step, this paper outlines the methodology to be followed by future researchers aiming to shed light on metaverse and business transformation. It proposes a framework to assist authors in organizing existing literature on metaverses and guide them in identifying future research avenues.
Keywords: Virtual reality; Augmented reality; Avatars; Digital twins; Virtual worlds